Pericranial Hinged Flap for Congenital Posterior Meningoencephalocele Closure - Atmaja, Tessa Miranda; Kreshanti, Prasetyanugraheni; Handayani, Siti; Bangun, Kristaninta (Lingkar Studi Bedah Plastik Foundation, 2013)
Background: Posterior meningoencephalocele is a complicated case that requires adequate method for closure of the defect. Congenital meningoencephalocele is a rare incidence estimated at 1:3000 to 10000 live births; with occipital encephaloceles are the most common. The method for closure should prevent leakage of cerebrospinal fluid (CSF) and coverage for the calvarial bone. Meningoencephalocele are treated by excising the non-functional brain tissue and closed the defect using thick connective tissue graft, alloplastic material and local flaps. The problems with closure are continuous leakage of cerebrospinal fluid and infection, especially when alloplastic material is used. In this case report, a pericranial flap is used to close the dura. Patient and Method: A neonate with occipital meningoencephalocele was consulted to the Plastic Surgery Department with wound dehiscence and recurrent herniation of brain tissue after undergoing first surgery by the neurosurgery team. On the second operation, a premilene mesh was placed which was later infected and causing wound dehiscence. We then close the defect using pericranial hinged flap and primary closure of the skin and subcutaneous tissue. Result: After the closure using pericranial hinged flap, there were no signs of infection and no CSF leakage. In 4 month follow up, the defect has completely healed. Summary: Closure of calvarial bone defect with pericranial-hinged flap provides a tight closure of the intracranial space, without increased risk of infection. Pericranial hinged flap should be considered as a method of choice for closure of intracranial defect, preventing leakage of cerebrospinal fluid and reducing risk of infection.